Toward More Accessible and Inclusive Social Assistance Delivery : A Geospatial Analysis in the Philippines - Kawasoe, Yasuhiro (World Bank, Washington, DC, 2022)
The Philippines’ experience in implementing the social amelioration program (SAP) in response to the Coronavirus disease 2019 (COVID-19) pandemic highlights the pressing need for financial inclusion, especially among the poor. The absence of a national identification (ID) system and low bank account ownership posed a challenge in the delivery of SAP. The Government of the Philippines (GoP) expedited the development and registration for the national ID system (PhilSys) and used the opportunity to facilitate bank account opening. Not only ownership of bank or mobile money accounts but also accessibility to financial services is essential for financial inclusion. This study assesses the challenges and opportunities in financial inclusion, especially among the poor in remote communities. First, the study carries out a mapping of all financial transaction points and estimates the travel time to the nearest point. Second, the map is superimposed with the poverty and potential vulnerability of families in remote communities. Finally, the study assesses the coverage of 4Ps in remote areas in view of the potential challenges in implementing the social assistance program in hard-to-reach communities.